Carbon Sequestration Studies at Nagpur Municipal Corporation‘s Water Treatment Plant at Pench I & II by Existing Greenbelt - Joshi, M P; Grignon, Melanie; Devarkar, V D; Pande, Rucha (Plantae Scientia, 2020)
Carbon sequestration describes long-term storage of carbon dioxide or other forms of carbon to either mitigate or defer global warming and avoid dangerous climate change. Present study deals with the absorption of the atmospheric carbon in the study area selected by selecting planting methods that return biomass to the soil and enhance the conditions in which the carbon within the plants will be reduced to its elemental nature and stored in a stable state through Green belts. It is calculated that, Carbon Absorption by Green Belt Carbon absorption rate is approximated 49.27 kg per mature plant per year as per international standards. As per CPCB (2000) Guidelines, the trees to be planted are 1250 plants per acre, 1250 trees will absorb 1250 X 49.27 = 61587.50 kg of carbon per year per Acer. Project Site (Pench I & II - 1.16 acre) has sequestered 18724 kg of carbon per Acre.